ESD with double clips and rubber band traction of neoplastic lesions developed in the appendiceal orifice is effective and safe - Oung, Borathchakra; Rivory, Jérôme; Chabrun, Edouard; Legros, Romain; Faller, Julien; Léger-Nguyen, Florence; Rostain, Florian; Ber, Charles-Eric; Hervieu, Valérie; Saurin, Jean-Christophe; Ponchon, Thierry; Jacques, Jérémie; Pioche, Mathieu (Endoscopy International Open, 2020)
Background and study aims Endoscopic submucosal dissection (ESD) of superficial colorectal lesions in close proximity to the appendiceal orifice (L-PAO) was shown to be feasible except in case of deep invasion into the appendix (type 3 of Toyonaga’s classification). This study aimed to determine the outcomes of ESD with double clip and rubber band traction (DCT-ESD) of L-PAO including a majority of type 3.Patients and methods We reviewed retrospectively all consecutive DCT-ESD of L-PAO performed in 3 French centers. Each lesion was described according to Toyonaga’s classification and type 0 lesions were excluded. The primary outcome was en bloc and R0 resection rates for L-PAO. Morbidity and salvage surgery were recorded.Results A total of 32 patients underwent DCT-ESD; 22 lesions (68.8 %) were type 3, including 11 with previous appendectomy (34.4 %). Median lesion size was 35 mm range (10–110 mm) and median duration of resection was 47 min range (10–230 min). We achieved 100 % of En bloc resection exclusively with DCT-ESD and 90.6 % of histological R0 resection rate. Per-procedure, 11 perforations occurred and were all immediately closed with clips. Overall, 3 patients (10.7 %) underwent surgery without stoma (2 complications related and 1 incomplete resection). No death occurred.Conclusion ESD of lesions deeply invading appendiceal orifice is feasible with the help of a traction system. Technical success by endoscopy avoiding surgery was achieved in 90.6 % of cases.